Konflik Hukum Perkawinan Beda Agama di Indonesia (Studi Penetapan Hakim Nomor: 12/Pdt.P/2022/Pn Ptk) - Adella Yuana; Ilka Sandela (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
Article 1 of Law Number 1 of 1974 concerning Marriage (hereinafter referred to as the Marriage Law) which states